Educational researchers’ perceptions of editorial ethics and attitudes in Turkish academic journals: a mixed-methods study - Gülsüm Sertel; Engin Karadag; S. Koza Ciftci (International Journal for Educational Integrity)
Abstract This study aimed to determine editors’ attitudes toward the article publication process in educational journals. A convergent mixed-methods design was employed to achieve this. Data were collected from 179 faculty members working in the education faculties in Turkey. The data collection instruments included the Editorial Attitudes Assessment Scale, a questionnaire on demographic characteristics, and an open-ended question soliciting additional opinions on the subject matter. The results of the descriptive and comparative analyses were compared, interpreted, and integrated with the findings obtained from the supplementary views provided by the participants. The authors contend that there are significant ethical shortcomings in the editorial practices. To enhance awareness of the role, responsibilities, and scientific and social obligations of editors in the article publication process, editorial training, orientation, and incentives for editing can be implemented.